The Activity of Liposome-Parijoto Formula Through p53 Expression in HepG2 Cell Line - widyandani sasikirana; Ragil Setia Dianingati; Khairul Anam; eva annisaa'; evieta Rohana (Journal of Biomedicine and Translational Research, 2023)
Parijoto, one of Melastomaceae family, has been known to have cytotoxic activity in HepG2, a hepatocellular cancer cell line, but with low activity. However, the ethyl acetate fraction of Parijoto gave the highest antioxidant and cytotoxic activity in 4T1. Then, purification and liposome formulation need to be carried out to increase the activity of Parijoto extract.  Objective: This research aimed to study the cytotoxic activity and molecular mechanism of LEA (Liposom-Ethyl Acetate of Parijoto Fraction) in HepG2. Method: Extraction has been done by maceration, followed by partition using n-hexane, ethyl acetate, and methanol. LEA formulation was carried out by thin-layer hydration with modification and the formula was sized using a bath sonicator.  Cytotoxic activity test of LEA and extract was performed in five serial concentrations (3,9 µg/mL–250 µg/mL), while the positive control doxorubicin performed in 3,9 µg/mL – 250 µg/mL by MTT assay. P53 gene expression was analyzed by using PCR-electrophoresis. Result: Results showed that LEA increased the cytotoxic activity (IC50 = 28.40 μg/ml). Furthermore, based on the electrophoresis study, LEA induced the p53 expression while the extract only did not. Conclusion: Liposome formula from ethyl acetate fraction of Parijoto extract (LEA) was able to increase cytotoxic activity and p53 gene expression was possible through the apoptotic mechanism. This shows that this formula is a promising strategy to improve the bioavailability of herbal medicines as cytotoxic agents.